2019
DOI: 10.1590/1983-1447.2019.20180307
|View full text |Cite
|
Sign up to set email alerts
|

Características das quedas com dano em pacientes hospitalizados

Abstract: Objective: Describe the characteristics of falls in patients with damage, their risk factors and injuries. Method: Retrospective and longitudinal study of 260 records of falls with damage of adult patients in clinical and surgical units of a general hospital, from September 2012 to June 2017. Data were collected in May 2018 from the electronic fall and electronic record research instrument, and the statistical analysis was described.Results: There were 260 falls with damage, mostly in the elderly (78%), female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 14 publications
1
1
0
19
Order By: Relevance
“…25 With respect to multimorbidity, continuous use of medications, frailty, dependence for BADL and IADL, and the high proportion of older people in this research with these conditions is in accordance with studies that point out the presence of diseases, use of medications, frailty, and dependence as important factors for the risk of falls. 26,27 Regarding the characteristics of the falls of the participants in the current study, it was observed that they are similar to the characteristics found in another study conducted in Brazil 28,29 , as well as and in a study conducted in South Korea 30 , both with hospitalized individuals. These studies revealed that the majority of falls occur from the faller's own height and in the bedroom, which makes it possible to target preventive measures, especially environmental measures.…”
Section: Discussionsupporting
confidence: 85%
“…25 With respect to multimorbidity, continuous use of medications, frailty, dependence for BADL and IADL, and the high proportion of older people in this research with these conditions is in accordance with studies that point out the presence of diseases, use of medications, frailty, and dependence as important factors for the risk of falls. 26,27 Regarding the characteristics of the falls of the participants in the current study, it was observed that they are similar to the characteristics found in another study conducted in Brazil 28,29 , as well as and in a study conducted in South Korea 30 , both with hospitalized individuals. These studies revealed that the majority of falls occur from the faller's own height and in the bedroom, which makes it possible to target preventive measures, especially environmental measures.…”
Section: Discussionsupporting
confidence: 85%
“…(6,(13)(14) Em contrapartida, alguns autores encontraram uma maior prevalência de quedas entre as mulheres e associaram a uma maior prevalência de doenças crônicas, maior incidência de osteoporose e alterações de ordem hormonal na pós-menopausa, fatores que interferem no equilíbrio postural, bem como na redução de massa muscular. (7,15) Com relação à faixa etária, os pacientes que sofreram quedas apresentaram idade igual ou superior a 60 anos (50,6%). Sabe-se que o avanço da idade desencadeia uma série de alterações fisiológicas, consideradas fatores de risco para a ocorrência de quedas, mais frequentes nessa faixa etária.…”
Section: Discussionunclassified
“…Os fatores comumente observados são aqueles relativos à instabilidade postural, alteração da marcha, diminuição da cognição, déficits sensoriais, além dos agravos crônico-degenerativos. (6)(7) Os dados epidemiológicos apontam que cerca de um terço dos idosos sofre ao menos uma queda ao ano. (16) As quedas cometem cerca de 30% dos idosos acima de 60 anos e de 40 a 50% dos idosos mais velhos (acima de 80 a 85 anos), consistindo na principal causa de lesões, fatais ou não, nesses grupos.…”
Section: Discussionunclassified
See 2 more Smart Citations